Monitoring and Evaluation of the Implementation of the Arabic Language Learning Curriculum in Madrasa - Iis Susiawati; Ubaid Ridlo; Dadan Mardani (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study uses a descriptive qualitative approach in examining the facts and phenomena that occurred at MA Al-Irsyad Al-Islamiyah Haurgeulis related to monitoring and evaluation issues. The research method used is a field study, with data collection techniques through observation, interviews and documentation. This study aims to determine the planning and implementation of learning as well as monitoring and evaluating the implementation of the Arabic language learning curriculum at the Madrasah Aliyah. Several things that can be concluded are: 1) Learning planning is done quite well with the accuracy of the schedule and completeness of existing learning tools, 2) Implementation of learning which includes the learning process for 1 semester , evaluation of learning by teachers and documentation of learning process activities, all running according to the curriculum, 3) Monitoring and evaluation which includes evaluation of the implementation of learning can be judged to be quite good based on the results of the assessment rubric filled by students against Arabic language teachers in carrying out the teaching and learning process in the classroom. Likewise, monitoring and evaluation of learning by the principal of the teacher is carried out at the end of each semester